Akuntansi Lingkungan Sebagai Suatu Sistem Informasi: Studi Pada Perusahaan Gas Negara (PGN) - Anak Agung Gde Satia Utama (Faculty of Economic and Business, 2016)
Environmental Accounting as Information System: Study at Perusahaan Gas NegaraThe purpose of this research is to explore environmental accounting information systems at Perusahaan Gas Negara (PGN). The specific objectives of this research are to know the company already exist to environmental accounting implementation, to obtain cost of environmental at PGN get positive significant revenue, and also describe a model of environmental accounting information systems. According to the results, PGN already exist environmental accounting. It was found in company’s annual report. The information of environmental cost get positive impact to revenue and show the model of environmental accounting information systems at PGNDOI: 10.15408/ess.v6i1.3123